Aktualisasi Pengurangan Stunting Balita Melalui Sosialisasi Dan Pemberian Makanan Tambahan (PMT) Di Desa Mentor Kabupaten Probolinggo - Aristyana Vira Anggraini; Khoirotun Annisah; Balqista Safia Haya; Adhitya Novrizal Firmanda; Shieva Anandia; Kalvin Edo Wahyudi (Pusat Riset dan Inovasi Nasional, 2023)
One of the efforts that can be made in order to reduce the stunting rate that occurs in toddlers is through the provision of supplementary food (PMT). Stunting is a problem related to nutrition caused by a lack of fulfillment of nutritional needs due to inadequate food intake. Therefore, the purpose of this study is to provide socialization regarding the provision of supplementary food (PMT) for toddlers. The target of this activity is as many as 50 mothers and their toddlers who fall into the stunting category in Mentor Villages who are selected based on data from village midwives in each hamlet. Several menus were distributed during the Socialization of Additional Menus (PMT), including Moringa leaf pudding, pumpkin pudding, dragon fruit creamy jelly, chicken martabak, and chicken dumplings. The research method used in this study went through 4 stages, namely observation, planning, outreach and evaluation. The data collection technique uses a questionnaire method in the form of a pre-test. The sampling results show that 1.) the majority of mothers have paid attention to the nutritional composition of toddlers, 2) the majority of mothers are still not consistent in paying attention to the amount and type of food ingredients given to toddlers, 3) the majority of mothers under five are able to make varied and interesting food for consumption by toddlers, but not routinely done every day, 4) the majority of mothers have paid attention to their children's food patterns on a daily basis, 5) the majority of mothers have carried out good supervision and assistance in terms of food for their children his son.